BILINGUALISME DAN DIGLOSIA DALAM ACARA NJAJAH DESO MILANG KORI RADIO ISMOYO PALEMBANG SERTA IMPLEMENTASINYA DI MTs ROUDHOTUL MUBAROKAH OKI DENGAN MENGGUNAKAN MEDIA INTERNET - Nurhayati, Dwi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The problem in this research is how is bilingualism and diglosia in the program Njajah Deso Milang Kori Radio Ismoyo Palembang. The purpose of this research is to know and describe bilingualism and diglosia in the program Njajah Deso Milang Kori Radio Ismoyo Palembang. The method used is descriptive method. The data source of this research is Ismoyo Palembang's broadcaster and radio listener. The data collection techniques used in this study were the techniques of referring skillful involvement, recording techniques, and recording techniques. The validity technique of the data used in this study is triangulation technique. The data analysis technique used in this study is a qualitative analysis technique. The results showed that there were three broadcasters and listeners who became bilingualism, namely announcer 1 using Javanese and Indonesian, broadcasters 2 using Javanese and Indonesian languages, listeners 4 using Javanese and Sudanese. Whereas twelve people (60%) experienced diglosia. Furthermore, people with diglosia leak were eight people (40%).And the application of this study has an effect on students at MTs Roudhotul Mubarokah OKI.